2016
DOI: 10.2337/db15-1550
|View full text |Cite
|
Sign up to set email alerts
|

Leptin Substitution in Patients With Lipodystrophy: Neural Correlates for Long-term Success in the Normalization of Eating Behavior

Abstract: Lipodystrophy (LD) is a rare disease with a paucity of subcutaneous adipocytes and leptin deficiency. Patients often develop severe diabetes and, additionally, show a disturbed eating behavior with reduced satiety. The disturbed eating behavior can be restored by substitution with the leptin analog metreleptin. Long-term effects of metreleptin on resting state brain connectivity in treatmentnaive patients with LD have not been assessed. In this study, resting state functional MRI scans and extensive behavioral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
38
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(47 citation statements)
references
References 34 publications
9
38
0
Order By: Relevance
“…Regarding energy intake, in ob/ob mice and lean rodents, leptin replacement decreases caloric intake 9 , 37 , 56 . Similarly, in severe hypoleptinemic populations with CLD or GL, leptin decreases robust food intake by affecting hedonic and homeostatic nervous centers that control satiety and hunger feeling 31 , 57 , 58 . In lean women with mild acquired hypoleptinemia, leptin administration reduces salience, attention, and rewarding value of food 59 .…”
Section: Discussionmentioning
confidence: 99%
“…Regarding energy intake, in ob/ob mice and lean rodents, leptin replacement decreases caloric intake 9 , 37 , 56 . Similarly, in severe hypoleptinemic populations with CLD or GL, leptin decreases robust food intake by affecting hedonic and homeostatic nervous centers that control satiety and hunger feeling 31 , 57 , 58 . In lean women with mild acquired hypoleptinemia, leptin administration reduces salience, attention, and rewarding value of food 59 .…”
Section: Discussionmentioning
confidence: 99%
“…In the fasting compared to the fed state 46 hypothalamic-PFC functional connectivity was enhanced, while the ingestion of a meal reduced functional connectivity to the medial and lateral PFC 45, 47 . Interestingly, other hormonal interventions with leptin 48, 49 or intranasal oxytocin 50–52 have likewise shown to alter PFC functional connectivity. Leptin replacement therapy in patients with lipodystrophy, for example, significantly increased hypothalamic-PFC functional connectivity accompanied by normalization of eating behavior 49 .…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, other hormonal interventions with leptin 48, 49 or intranasal oxytocin 50–52 have likewise shown to alter PFC functional connectivity. Leptin replacement therapy in patients with lipodystrophy, for example, significantly increased hypothalamic-PFC functional connectivity accompanied by normalization of eating behavior 49 . Accordingly, in the current study we found the functional connection between the anterior medial PFC and the hypothalamus to increase in participants with favorable peripheral insulin sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…Paired biopsy studies have shown that nonalcoholic steatohepatitis associated with GLD was ameliorated with metreleptin treatment [ 75 , 76 ]. During 52 weeks of metreleptin treatment, improved brain connectivity associated with hedonic and homeostatic control of eating behavior, decreased hunger, and increased satiety were observed [ 77 ].…”
Section: Treatment Approach For Lipodystrophymentioning
confidence: 99%